LiNi0.5Mn1.5O4 high-voltage cathode coated with Li4Ti5O12: a hard X-ray photoelectron spectroscopy (HAXPES) study. Issue 47 (13th November 2015) - Sachs, Malte; Gellert, Michael; Chen, Min; Drescher, Hans-Jörg; Kachel, Stefan Renato; Zhou, Han; Zugermeier, Malte; Gorgoi, Mihaela; Roling, Bernhard; Gottfried, J. Michael
Abstract : A Li4 Ti5 O12 coated LiNi0.5 Mn1.5 O4 high-voltage cathode was depth profiled by hard X-ray photoelectron spectroscopy after electrochemical cycling. Abstract : A Li4 Ti5 O12 (LTO) film was coated as buffer layer onto a LiNi0.5 Mn1.5 O4 (LNMO) high-voltage cathode, and after cycling of the cathode in a battery electrolyte, the LTO film was investigated by means of synchrotron radiation based hard X-ray photoelectron spectroscopy (HAXPES). By tuning the photon energy between 2 keV and 6 keV, we obtained non-destructive depth profiles of the coating material with probing depths ranging from 6 nm to 20 nm. The coating was found to be covered by a few nanometers thin surface layer resulting from electrolyte decomposition. This layer consisted predominantly of organic polymers as well as metal fluorides and fluorophosphates. A positive influence of the Li4 Ti5 O12 coating with regard to the size and stability of the surface layer was found. The coating itself consisted of a uniform mixture of Li(i ), Ti(iv ), Ni(ii ) and Mn(iv ) oxides that most likely adopted a spinel structure by forming a solid solution of the two spinels LiNi0.5 Mn1.5 O4 and Li4 Ti5 O12 with Li, Mn, Ni and Ti cations mixing on the spinel octahedral sites. The diffusion of Ni and Mn ions into the Li4 Ti5 O12 lattice occurred during the heat treatment when preparing the cathode. The doping of Li4 Ti5 O12 with the open d-shell ions Ni 2+ (d 8 ) and Mn 4+ (d 3 ) should increase the electronic conductivity of the coating significantly, as was found in previous studies. The complex signal structure of the Ti 2p, Ni 2p and Mn 2p core levels provides insight into the chemical nature of the transition metal ions.